2021
DOI: 10.1155/2021/4896282
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Long Noncoding RNA and mRNA Profiles in Subjects with the Phlegm-Dampness Constitution

Abstract: Background. Constitution in traditional Chinese medicine (TCM) plays a key role in the genesis, development, and prognosis of diseases. Phlegm-dampness constitution (PDC) is one of the nine constitutions in TCM, susceptible to metabolic disorders, which is mainly manifested by profuse phlegm, loose abdomen, and greasy face. Epidemiologic, genomic, and epigenetic studies have been carried out in previous works, confirming that PDC represents a distinctive population with microcosmic changes related to metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This finding indicates a potential risk of metabolic disorders in individuals with the PDC [ 37 ]. In recent years, studies on molecular mechanisms (e.g., DNA methylation, RNA, intestinal flora) have demonstrated, in several aspects, that PDC formation is associated with insulin resistance, oxidative stress, increase in free fatty acids, energy metabolism, endocrine disorders, genetics, and disorders in the metabolism of glucose and lipids [ [38] , [39] , [40] ]. In conclusion, the PDC is closely related to the occurrence and development of MAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding indicates a potential risk of metabolic disorders in individuals with the PDC [ 37 ]. In recent years, studies on molecular mechanisms (e.g., DNA methylation, RNA, intestinal flora) have demonstrated, in several aspects, that PDC formation is associated with insulin resistance, oxidative stress, increase in free fatty acids, energy metabolism, endocrine disorders, genetics, and disorders in the metabolism of glucose and lipids [ [38] , [39] , [40] ]. In conclusion, the PDC is closely related to the occurrence and development of MAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…A healthy lifestyle is essential to counteract the early stages of MAFLD [ 49 ]. The TCMC is also an important basis for predicting the progression, regression, and prognosis of a disease [ 38 ]. Also, study of the PDC is a good entry point to explore metabolic disorders [ 42 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial dysfunction is involved throughout the development of atherosclerosis and is a key link in its formation [17]. Studies have shown that sputum-dampness constitution presents the propensity of both insulin resistance, lipid metabolism as well as disorders of purine metabolism in the undiagnosed state [18], and considered that they are risk factors for the formation of atherosclerosis caused by vascular endothelial dysfunction induced by phlegm-dampness constitution .For example, patients with sputum-dampness constitution have decreased serum levels of HDL-C and increased levels of TC, TG, and LDL-C [19]. The elevation of blood lipids and cholesterol can directly induce endothelial cells to undergo oxidative stress and inflammatory reactions, resulting in endothelial dysfunction [20]; While insulin resistance can induce NOx activation to produce a large amount of oxygen free radicals and inhibit the activation of eNOS [21], thus aggravating endothelial function injury and accelerating the formation of atherosclerosis.…”
Section: Sputum-dampness Constitution and Vascular Endothelial Dysfun...mentioning
confidence: 99%
“…Epidemiologic studies have reported that phlegm-dampness constitution is highly related to diabetes and metabolic syndromes (MS) [9]. Genomic studies have illustrated that phlegm-dampness constitution has the molecular basis of metabolic disorder and is the potential risk for arteriosclerosis and thrombosis; the individuals are susceptible to hyperlipemia and diabetes [10], and various genes in the phlegm-dampness constitution are involved in glucose and lipid metabolism pathways [11]. In addition, single-nucleotide polymorphisms and methylation investigation have also confirmed that phlegm-dampness constitution is closely related to GLMD [12].…”
Section: Introductionmentioning
confidence: 99%